Virginal mammary hypertrophy in children and surgical treatment - Figueroa Ángel, Santino (2014)
Introduction: Virginal breast hypertrophy is a female condition frequently present during puberty as a fast growing breast that causes psychological, aesthetic and functional alterations. It is a benign breast pathology of difficult clinical diagnosis when present unilaterally, and its surgical treatment is still controversial. Methods: Five clinical cases of virginal breast hypertrophy were treated at Hospital Infantil de México Federico Gómez from 2009-2011. We present their clinical characteristics, surgical treatment, and results obtained. Results: Most patients had either superior or inferior pedicle mammary reduction with favorable results or no re-intervention due to recurrence. A patient had suspicion of phyllodes tumor and subcutaneous mastectomy was performed. The only complication was nipple areola complex necrosis in one patient. Conclusions: The surgical technique should be individualized in each patient according to characteristics, presentation, and personal objectives. Mammary reduction for adolescents with this pathology is a good option, with good aesthetic results, easily accepted by the pediatric patient, lowering morbidity of a second surgical procedure.